Potential impacts of a green revolution in Africa: The case of Ghana - Breisinger, Clemens; Diao, Xinshen; Thurlow, James; Al-Hassan, Ramatu M. (Wiley, 2011)
Agricultural growth in Africa has accelerated, yet most of this growth has been driven by land expansion. Land expansion potential is reaching its limits, urging governments to shift towards a green revolution type of productivity‐led growth. Given the huge public investments required, this paper aims to assess the potential impacts of a green revolution. Results from a CGE model for Ghana show that green revolution type growth is strongly pro‐poor and provides substantial transfers to the rest of the economy, thus providing a powerful argument to raise public expenditure on agriculture to make a green revolution happen in Africa. Copyright © 2009 John Wiley & Sons, Ltd.